ANALISIS USAHA TAMI FARM DENGAN ANALISIS KANVAS BISNIS MODEL - Musrifin, Mohammad; Pahlevi, Reza Widhar (Journal Competency of Business, 2022)
The purpose of this study was to determine the implementation of Etawa Goat farming techniques in the research area, as well as to analyze the Etawa Goat livestock business feasible to be cultivated in the research area, and to find out the obstacles faced by farmers and the efforts made to overcome these obstacles. The results of the study concluded that the implementation of the Etawa Goat cultivation technique at TAMI FARM Ranch was carried out intensively, namely goats were kept in cages continuously, feeding was carried out three times a day with predetermined formulations, the goat mating system was still carried out naturally, and traditional medicine was given so that goats always healthy and free from disease. Some of the obstacles faced by TAMI FARM farms are limited land and supply of feed. As for the efforts made by farmers to face obstacles, namely planting various types of grass for goat feed, as well as renting land for goats or for planting feed for goats.